Procedure to Validate Sexual Stimuli: Reliability and Validity of a Set of Sexual Stimuli in a Sample of Young Colombian Heterosexual Males - Pablo Vallejo-Medina (International Journal of Psychological Research, 2017)
Penile plethysmography – or phallometric assessment – is a very relevant evaluation for sexual health. The objective of this research is to suggest a guideline to validate sexual stimuli and validate a set of sexual stimuli to assess “normative” sexual behavior in Colombian young heterosexual men. Six videos of 3:15 minute-long were used. A total of 24 men were assessed. Objective sexual arousal, the International Index of Erectile Function-5, Self-Assessment Manikin, Multidimensional Scale to Assess Subjective Sexual Arousal and socio-psycho-sexual questions were used. The results showed three sexual excerpts which were clearly superior to the others – something discordant with the subjective opinion of researchers. These three sexual excerpts generated internally consistent measurements; moreover, good indicators of external validity have been observed with statistically significant differences as expected. Furthermore, with a small healthy Colombian young population, it has been shown that the three stimuli produce objective sexual arousal if used together.